UKF based high-precision data fusion approach of orthogonal IMU sensors. Issue 1 (March 2021) - Zhang, Xiaowen; Yuan, Shuai; Wu, Jian; Wang, Binzhuo; Sun, Yu
Abstract: Accurate attitude angle measurement is very important for some automatic robots, but the noise uncertainty in the sensor can cause measurement error. In order to solve the problem that these pose sensors have low estimation accuracy, this paper proposes a data fusion approach using the IMU sensor including gyroscope, accelerometer and magnetometer. Through placing multi-sensors with spatial orthogonal relation, global optimization is achieved, and the UKF algorithm is adopted to fuse data. This fusion uses the gyroscope data as the state vector, and regards the accelerometer and magnetometer data as the observation vector to improve the accuracy of attitude angle measurement. The experimental result is performed to compare the proposed method with traditional method, and the proposed method can obtain better attitude measurement accuracy, which illustrates the effectiveness of the proposed method.